Filtration аnd Viscous Creeping Seetlement оf Mesopotamia Loamy Soils - N. N. Baranov; Ali А. А. Al-Robai (Наука и техника)
The paper contains calculations for determination of values pertaining to full settlements with due account  of creeping phenomenon for a number of the Mesopotamia regions (Al-Diwaniya, Khidr and Hillah). Coefficients of filtration compaction have been accepted in accordance with engineering and geological research and creeping parameters have been accepted on the basis of the published data of the investigations (N. A. Tsytovich, Z. G. Ter-Martirosian et al.). The values obtained in calculations significantly exceed values that have been determined in accordance with the existing norms.